Transarterial embolisation of a large focal nodular hyperplasia, using microspheres, in a paediatric patient - Oliveira, C (2015)
Benign liver tumours are uncommon in children, haemangiomas being the most frequent. Focal nodular hyperplasia (FNH) represents about 2% of paediatric liver tumours. In children, as in adults, a conservative approach is generally recommended. However, large lesions (greater than 5 cm) are more frequent in the paediatric age group, and in these cases, as well as in growing lesions, surgical removal may be advised. Transarterial embolisation (TAE) has been a successful alternative option described in older patients, especially in cases where surgical removal is not possible. This minimally invasive procedure may also become an option in the paediatric group. The authors report the case of a boy with a large FNH treated with TAE using microspheres.